Physician-modified fenestration or in situ fenestration for preservation of isolated left vertebral artery in thoracic endovascular aortic repair - Shen, Peier; Li, Donglin; Wu, Ziheng; He, Yangyan; Wang, Xiaohui; Shang, Tao; Zhu, Qianqian; Tian, Lu; Li, Zhenjiang; Zhang, Hongkun (Frontiers in Cardiovascular Medicine, 2023)
Objective To present our experience of preserving the isolated left vertebral artery (ILVA) with physician-modified fenestration (PM-F) or in situ fenestration (ISF) during thoracic endovascular aortic repair (TEVAR) for aortic pathologies involving aortic arch. Methods This is a single-center, retrospective, observational cohort study. Between June 2016 and December 2021, 9 patients (8 men; median age 60.0 years old) underwent TEVAR with ILVA reconstruction (PM-F, n = 6; ISF, n = 3) were identified and analyzed. Results The technical success rate was 100%. No early (<30 days) death occurred. No aortic rupture, major stroke or spinal cord injury was observed. The median follow up was 38.0 (rang: 1.0–66.0) months. One death occurred at 56 months, while the reason cannot be identified. No aortic rupture, major stroke or spinal cord injury was observed during follow up. No patient required reintervention. Out of the 22 successfully revascularized target vessels, 2 ILVAs were found occluded in 2 patients at 6 months and 7 months, respectively. However, these two patients were asymptomatic. Conclusions Our initial experience reveals that PM-F or ISF for ILVA preservation was feasible, safe, and effective during TEVAR for complex thoracic aortic pathologies. However, the patency of preserved ILVA should be improved.